The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1007/s00167-017-4622-7
|View full text |Cite
|
Sign up to set email alerts
|

Modifications of femoral component design in multi-radius total knee arthroplasty lead to higher lateral posterior femoro-tibial translation

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 44 publications
(64 reference statements)
5
33
0
1
Order By: Relevance
“…Sensitivity analyses confirmed that hospital LOS was shorter among comparator device recipients. Although it is beyond the scope of this study to determine the exact reason for the decreased length of stay, the comparator device was designed to improve mid flexion stability [23], patellofemoral tracking [5,9e11] and has been shown to have improvements in PROMs on a broad spectrum of measures at 1 and 2 years [8]. It is possible that these features have contributed to patients mobilizing more rapidly and with greater confidence, potentially leading to the reduced length of stay demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity analyses confirmed that hospital LOS was shorter among comparator device recipients. Although it is beyond the scope of this study to determine the exact reason for the decreased length of stay, the comparator device was designed to improve mid flexion stability [23], patellofemoral tracking [5,9e11] and has been shown to have improvements in PROMs on a broad spectrum of measures at 1 and 2 years [8]. It is possible that these features have contributed to patients mobilizing more rapidly and with greater confidence, potentially leading to the reduced length of stay demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…29 A more recent in vivo study has shown improved lateral roll-back and eliminated paradoxical medial roll-forward compared with the PFC Sigma. 30 This implant has also demonstrated a shorter length of stay and decreased likelihood of requiring a skilled nursing facility on discharge, thus reducing overall hospital costs. 31 Previous studies have shown improved patellofemoral symptoms and crepitus with the ATTUNE compared with the PFC Sigma, [32][33][34][35] although little difference in clinical outcome or satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Die tatsĂ€chliche Rotationskinematik ist dabei vom tibialen Slope abhĂ€ngig und wenig vorhersagbar. Eine aktuelle Arbeit zeigt sogar, dass der femorale Kondylenradius einen höheren Einfluss auf die Rotationskinematik in einem mobilen Inlaykonzept hat als der eigentliche Rotationsmechanismus des Onlays [36]. In Bezug auf die niedrig konformen Inlays wurden Posterior-stabilized Prothesen entwickelt um ein gefĂŒhrtes posteriores Rollback zu schaffen und die Problematik der anterioposterioren InstabilitĂ€t zu adressieren [37].…”
Section: Tibiale Rotationskinematikunclassified